Praktik Pemberian Upah Kerja dalam Industri Tali Rafia: Tinjauan Hukum Islam terhadap Ketidakpastian Pembayaran Ujrah - Alfiani, Nurul; Kaco, Suardi; Malik, Abdul (Milkiyah: Jurnal Hukum Ekonomi Syariah, 2024)
The uncertainty of the wage payment (ujrah) of nylon plastic rope between entrepreneurs and labour prompted this research. The purpose of this study is to determine the practice of giving wages given by , nylon plastic rope entrepreneurs to workers and understand the review of Islamic law regarding the practice of giving work wages between nylon plastic rope entrepreneurs and workers. This research is descriptive qualitative. Data collection techniques are carried out by means of observation, interviews and documentation. The results of this study indicate that the practice of giving work wages is permissible (mubah). The practice of ujrah applied by the Rajawali Rafia Rope entrepreneurs to workers who roll nylon plastic rope is that initially there is an agreement that if the worker has reached the predetermined roll target of approximately 1000 rolls, then the work wage will be given. But in practice, the wage paid depends on how fast the nylon plastic rope is sold. If the sales of nylon plastic rope in the Tali Rafia Rajawali business are sold quickly, the work wages will be given quickly. Although there is no clarity on the time of payment of wages, they still work as labourers.